Electrocardiographic changes after completion of a triathlon. Issue 3 (24th January 2020) - Hosatte‐Ducassy, Caroline; Correa, José A.; Lalonde, François; Mohindra, Rohit; Marton, Gregory; Chetrit, Michael; Marcotte, Audrey; Tournoux, François; Bridges, Eileen
Abstract: Objectives: Given the increasing popularity of long‐distance triathlon events among amateur athlete and the difficulty for emergency physician to address cardiovascular complaints in the context of exercise, this study aims to determine the prevalence of ECG changes after a long‐distance triathlon. Methods: This prospective observational study examines the prevalence of selected standard 12‐lead ECG findings, the Seattle criteria, in asymptomatic athletes before and after the completion of a long‐distance triathlon. Results: Of 99 ECGs obtained prior to the race, 28 were abnormal, for a pre‐race prevalence of 28.3% (95% CI [20.4, 37.8]). Of the 72 ECGs post‐race, 12 were abnormal, for a post‐race prevalence of 16.7% (95% CI [9.8, 26.9]). Common findings were increased QRS voltage significant for left ventricular hypertrophy (LVH) (24 [24.2%] pre‐race, 10 [14.1%] post‐race), early repolarization (21 [21.2%] pre‐race, 19 [26.8%] post‐race), and incomplete right bundle branch block (RBBB) (8 [8.1%] pre‐race, 11 [15.5%] post‐race). McNemar's test showed no agreement between the ECG pre‐ and post‐results ( χ 2  = 6.54, P  = .01), suggesting a possible effect of the race on ECG findings. Conclusion: Long‐distance triathlon might acutely affect the ECGs findings in asymptomatic athletes, and abnormal ECG findings were common in our cohort of athletes.